ROMANIAN ACCOUNTING - A TALE OF TWO STANDARDS - MARIUS DEAC (Annals of the University of Petrosani: Economics)
The process of accounting harmonization in Europe has started in 1978 with the adoption of the Fourth Council Directive 78/660/EEC regarding the annual accounts of limited liability companies. The harmonization process continued with the regulation of the consolidated annual accounts with the enactment of the Seventh Council Directive 83/349/EEC. In 2002 the European Parliament has adopted the EC Regulation No. 1606/2002 requiring all listed group entities within EU to apply the International Accounting Standards for their consolidated financial statements starting from 2005. This has led to the use of a dual accounting standardization as listed entities are required to use IAS/IFRS while non-listed entities use the national GAAP harmonized with the 4th and 7th directives. The adoption of the new accounting directive 2013/34/EU does not solve this differentiation as it doesn't allow the option for national accounting regulators the use of IFRS for SMEs. Romania, as a member of the European Union, is no exception from this usage of a dual accounting standard. After the fall of the communist regime, Romania has modernized its accounting system by adopting a French inspired, EU 4th directive compliant national GAAP. Between 2001 and 2005 there was a strong interest towards the adoption of IAS/IFRS that went beyond the scope of EC Regulation No. 1606/2002. This has changed in 2005 when IAS/IFRSs were considered as an option of additional voluntary disclosure. From 2006, Romania has aligned its national legislation to the requirements of EC Regulation No. 1606/2002. The application of this dual standard accounting system has been cumbersome especially for the entities that were required to prepare two different annual accounts, one using IAS/IFRS and one using Romanian GAAP. This obstacle has been overcome in 2012 when certain entities were allowed to prepare their financial statements using only IFRS.